Characterization of Tamarind Seed Polysaccharide Hydrolyzed with Cellulase and β-Galactosidase - ZHENG Weiqi, GAO Xing, SHE Haocheng, WANG Jingyi, LI Jie, ZHANG Hui, XIONG Zhiqiang, AI Lianzhong, XIE Fan (Shipin Kexue)
In order to improve some physicochemical properties of tamarind seed polysaccharide (TSP) and to further expand its application in food packaging and biological materials, TSP (T-0) was subjected to three enzymatic treatment: hydrolysis with cellulase for 0.5 h (CT-0.5), β-galactosidase for 8 h (GT-8), and GT-8 followed by CT-0.5 (ET-8 + 0.5), yielding xyloglucans with different molecular masses and side chain structures. The correlation mechanism between the structural characteristics (monosaccharide composition, molecular mass, conformation, particle size and turbidity) of the xyloglucans and their functional behaviors (rheology and micromorphology) was systematically analyzed. The results showed that the molecular chain rigidity of the xyloglucans followed the order CT-0.5 > T-0 > GT-8 > ET-8 + 0.5. For GT-8 and ET-8 + 0.5, hydrophobic aggregation occurred due to partial galactose removal, and the molecular chain tended to be spherical with increased flexibility, resulting in an increase in average particle size and turbidity. The average particle size and turbidity of CT-0.5 decreased because the main chain was shortened, the molecular chain was more stretched and the rigidity was increased. Rheological results showed that the apparent viscosity of the xyloglucans was significantly lower than that of TSP. Notably, both GT-8 and ET-8 + 0.5 were capable of forming gels at a concentration of 2%, whereas CT-0.5 formed temperature-sensitive gels at the same concentration. Accordingly, the enzymatic treatments changed the gel properties of TSP. Under scanning electron microscopy (SEM) and fluorescence microscopy (FM), TSP, GT-8 and ET-8 + 0.5 all exhibited a network structure with intermolecular cross-linking. GT-8 and ET-8 + 0.5 showed hydrophobic aggregation, while CT-0.5 showed a fibrous rod-like structure with weakened intermolecular cross-linking. These findings demonstrate that the enzymatically prepared tamarind seed xyloglucans have good gel properties, thereby holding great potential for applications in food packaging and biological materials.